Time and politics in Elias Canetti - Speziale, Tomás (2023)
This article studies the link between time and politics in the Works of Elias Canetti, to claim that the political dimensión of his thought is constituted, in part, by the non-manipulable face of temporality. In other words, we seek to make evident that politics in Canetti is not reduced to the present because it is simultaneously constituted and exceeded by the infinity of the past and the future. To be what it is, politics must deal with that absolute excess. So, we will systematically and critically review a series of background texts that have omitted or displaced this paradoxical relation between time and politics, and, in opposition to these proposals, we will state that the political question in his texts revolves around the overflow of the living present by the infinity of the past and the future.